Análise e controle de aerogeradores com conversor pleno durante afundamentos de tensão - Gabe, Ivan Jorge (2012)
This thesis addresses the main issues regarding the operation of full power converters wind turbines connected to the grid under balanced and unbalanced voltage sags. In the past, the grid codes allowed wind turbines to be disconnected during voltage and frequency disturbances. However, recently, grid codes updates often require that wind turbines remain connected during voltage sags aiming to provide voltage back-up support. Furthermore, some specific criteria establish that wind turbines should be able to utilize part of its current capability to promote the voltage back-up during unbalanced voltage sags. To guarantee the grid connected converter operation, even with voltage sags that lead to zero-voltage situations and unbalanced voltage conditions, a synchronous frame PLL with a very low time constant is designed and adapted with a Kalmam filter synchronization system. This thesis propose a two stages synchronization for grid connected converters that is able to ensure proper operation of the converter even when voltage on the converter terminals has temporarily falling down to zero. This goal is meet with a synchronous frame PLL with a very low time constant adapted with a Kalmam filter synchronization system. This composed synchronization system allows the converter control system to get the positive and negative sequences voltages components, that are necessary to the output power control even under severe voltage dips. Moreover, an anti windup is adapted to operate with a resonant current controller enabling the minimization of the saturation in the control action during voltage transients. During unbalanced voltage dips, the injection of unbalanced currents to the voltage back-up support becomes a good alternative to reduce the imbalance factor of the grid voltages. However, it is necessary to limit the maximum current output of the converter to avoid undesirable protection trips. This thesis proposes a strategy that limite the output currents allowing the use of the converter full current capacity during unbalanced voltage sags support. To achieve this goal, the current references are divided into three parts. The former is associated with the active power reference synchronized with the positive sequence voltage. The second is the reactive power synchronized with the positive sequence voltage and the third is the reactive power synchronized with the negative sequence voltage. The strategy propose the computation of th reactive power references by the positive and negative sequence voltages on the PPC in order to not overpass the converter current limits. Experimental and simulation results corroborate the contributions of this thesis.